2015
DOI: 10.1259/dmfr.20140352
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CBCT enhancement filters on diagnosis of vertical root fractures: a simulation study in endodontically treated teeth with and without intracanal posts

Abstract: Objectives: To evaluate the influence of CBCT enhancement filters on the diagnosis of vertical root fractures (VRFs) in teeth with and without metal posts. Methods: The crowns of 40 uniradicular human teeth were removed and all roots were prepared. 20 teeth were randomly selected, and VRFs were induced using a universal testing machine. The i-CAT (Imaging Sciences International, Hatfield, PA) CBCT was used to scan teeth with and without intracanal metal posts using the following parameters: 0.2 voxel size, 8 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 30 publications
5
36
1
2
Order By: Relevance
“…() and Ferreira et al . () reported the influence of CBCT filters on vertical root fracture detection, which was not a condition simulated in the present study, and concluded that there was no significant difference when applying some XoranCat ® filters. Although this endodontic complication was not considered in the present study, their results are in agreement with the present results, except for the fractured file group.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…() and Ferreira et al . () reported the influence of CBCT filters on vertical root fracture detection, which was not a condition simulated in the present study, and concluded that there was no significant difference when applying some XoranCat ® filters. Although this endodontic complication was not considered in the present study, their results are in agreement with the present results, except for the fractured file group.…”
Section: Discussionmentioning
confidence: 54%
“…, Ferreira et al . ). However, there is a lack of information on CBCT filter performance in detecting several endodontic complications, justifying the importance of the present study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…, Ferreira et al . ). In the present study, the diagnosis of VRF was compromised by the presence of metallic posts and gutta‐percha, in accordance with previous studies (Costa et al .…”
Section: Discussionmentioning
confidence: 97%